IN VITRO ANALYTICAL EVALUATION OF NITROSAMINE – A CARCINOGENIC IMPURITIES IN OLMESARTAN MEDOXIMIL BY GC MS/MS METHOD - SARADHI, NDVR; KUMAR, K KALYAN; REDDY, M VENKATA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A simple and sensitive method development and validation for the simultaneous determination of the N-nitrosamine dimethylamine (NDMA) and N Nitrosamine diethylamine (NDEA) in Olmesartan medoxomil (OLM) API and formulations by a tandem mass spectrometer (GC-MS/MS). Methods: Gas chromatography with a programmed oven temperature controller, Elite Wax (30 m × 0.25 mm × 0.5 μm) column, Helium as carrier gas and hyphenated to the tandem mass spectrometer powered with triple quadrupole mass analyzer, and photomultiplier tube detector. The method was validated as per the United States Food and Drug Administration (USFDA) guidelines. Results: With the selected GC-MS/MS conditions, the NDMA and NDEA 0.08 μg/ml (80 ng/ml) and 0.16 μg/ml (160 ng/ml) injected and Rt. for NDMA 5.634 and NDEA 6.516 min, respectively. A linear/range lies in between 0.024 and 0.120 μg/ml and 0.048 and 0.240 μg/ml for NDMA and NDEA with r2 >0.99. The precision, accuracy, and system suitability are established as per USFDA and ICH guidelines, the sensitivity of NDMA limit of detection and limit of quantification 0.08, 0.024 and NDEA 0.16, 0.048. Conclusion: Other nitrosamine impurities are not involved in the determination of NDMA and NDEA in the OLM using GC-MS/MS and the method is simple, sensitive, rapid, accurate, and precise.